Analysis Of Promethee Methods On Assistance Recipients Family Of Hope Program In Poor People - Muhammad Hendrik Koto; Wahyu Riansah (Ali Institute or Research and Publication, 2025)
The Family of Hope Program (PKH) managed by the Ternate City Social Service is a critical social assistance initiative aimed at reducing poverty and improving the welfare of underprivileged families. However, the program's implementation is not optimal due to the lack of a systematic approach in the selection of beneficiaries. Currently, the process relies on manual home visits and subjective visual assessments, which are time-consuming and prone to inaccuracies. This research aims to develop a decision support system (DSS) that utilizes the Promethee method to enhance the objectivity and efficiency of the beneficiary selection process. The Promethee method was chosen for its ability to rank alternatives based on multiple criteria, making it suitable for handling complex decision-making scenarios. Four criteria—age, marital status, education, and disability—were used to evaluate and prioritize potential beneficiaries. This research involved data collection from the Ternate City Social Service, followed by system design and analysis using the Promethee approach. The findings indicate that the Promethee-based DSS provides a structured and transparent mechanism for evaluating candidates, enabling the Social Service to make more accurate and equitable decisions. This system significantly reduces the time required for the selection process while improving its reliability. The study concludes that integrating the Promethee method into the Family of Hope Program can address existing inefficiencies and support the Social Service in achieving its goal of targeted poverty alleviation